2016
DOI: 10.1016/j.chemosphere.2015.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Copper and cobalt mobility in soil and accumulation in a metallophyte as influenced by experimental manipulation of soil chemical factors

Abstract: The influence of Fe oxides, Mn oxides and organic matter (OM) on the Cu and Co mobility in soil and accumulation in the metallophyte Anisopappus chinensis (Ac), as compared with Helianthus annuus (Ha), was experimentally investigated. Growth and accumulation response when increasing the exchangeable Cu and Co concentrations in soil were also investigated. Plants were cultivated on soil where concentrations of Cu, Co, Fe oxides, Mn oxides and OM content were varied according to 36 treatments. The OM supply decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 68 publications
(93 reference statements)
2
26
0
1
Order By: Relevance
“…Thus, of the total extracted metals, 25% of Cd, 9% of Pb and 48% of Cu were considered to be mobile and thus bioavailable in Cam Pha rice paddy soils. These results correlate with previously published results from plant growth experiments in the presence of elevated metal cation concentrations [29,37,49].…”
Section: Sequential Extraction Of CD Cu and Pb From Cam Pha Rice Padsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, of the total extracted metals, 25% of Cd, 9% of Pb and 48% of Cu were considered to be mobile and thus bioavailable in Cam Pha rice paddy soils. These results correlate with previously published results from plant growth experiments in the presence of elevated metal cation concentrations [29,37,49].…”
Section: Sequential Extraction Of CD Cu and Pb From Cam Pha Rice Padsupporting
confidence: 92%
“…Rice grains from each variety were planted in sterile 15 mL Falcon ® tubes, containing 10 mL of solid RGM control, or with a corresponding trace metal content added. Nitrate and sulfate do not have effect on the experiment given the chosen pH (e.g., [8,28,29]).…”
Section: Experiments Of Rice Plant Growthmentioning
confidence: 99%
“…The results of the 2 plant growth trials discussed showed a related pattern. The reason for the difference in Co mobility in this seep soil + Fe‐WTR combination is unclear, and it is difficult to provide a speculative explanation for other than perhaps something linked to a possibly different organic matter component present in the Fe‐WTRs that is released when mixed with the seep 1 soil because organic matter differences have been reported to have the potential to mobilize soil Co (Lange et al 2016). This warrants further investigation on the mechanisms involved because it would be anticipated that Co in solution would be decreased following treatment and that the amendments would immobilize Co in the soil solution because WTRs have been shown to have the ability to adsorb Co (Chiang et al 2012).…”
Section: Discussionmentioning
confidence: 96%
“…(Cu = 0.99 mg/kg). According to Lange et al (2016), Cu mobility is mainly influenced by OM in soils. Indeed, increasing organic compost did enhance a decrease of Cu solubility.…”
Section: Influence Of Ph and Om On Soluble Cu In Soil Contaminated Bymentioning
confidence: 99%